Extreme swings of the South Pacific Convergence Zone and the different types of El Niño events. Issue 13 (10th July 2014) - Borlace, Simon; Santoso, Agus; Cai, Wenju; Collins, Matt
Abstract There have been three extreme equatorward swings of the South Pacific Convergence Zone (SPCZ) during the satellite era. These zonal SPCZ (zSPCZ) events coincided with an El Niño of different magnitude and spatial pattern, in which strong anomalous warming reduced the off‐equatorial‐to‐equatorial meridional sea surface temperature (SST) gradient near the dateline, enabling convection to shift equatorward. It is not known, given the short observational record, how and whether different types of El Niño are associated with zSPCZ events. Using perturbed physics ensembles experiments in which SST biases are reduced, we find that zSPCZ events are concurrent with notable eastern Pacific (EP) warming. Central Pacific warming alone is rarely able to produce a swing, even as the climate warms under a CO2 increase scenario. Only El Niño events with strong EP warming can shift the convective zone. Such co‐occurring events are found to increase in frequency under greenhouse warming.